Cohort differences on the CVLT-II and CVLT3: Evidence of a negative Flynn effect on the attention/working memory and learning trials. Issue 3 (20th March 2021) - Graves, Lisa V.; Drozdick, Lisa; Courville, Troy; Farrer, Thomas J.; Gilbert, Paul E.; Delis, Dean C.
Abstract: Objective: Although cohort effects on IQ measures have been investigated extensively, studies exploring cohort differences on verbal memory tests, and the extent to which they are influenced by socioenvironmental changes across decades (e.g. educational attainment; ethnic makeup), have been limited. Method: We examined differences in performance between the normative samples of the CVLT-II from 1999 and the CVLT3 from 2016 to 2017 on the immediate- and delayed-recall trials, and we explored the degree to which verbal learning and memory skills might be influenced by the cohort year in which norms were collected versus demographic factors (e.g. education level). Results: Multivariate analysis of variance tests and follow-up univariate tests yielded evidence for a negative cohort effect (also referred to as negative Flynn effect) on performance, controlling for demographic factors ( p = .001). In particular, findings revealed evidence of a negative Flynn effect on the attention/working memory and learning trials (Trial 1, Trial 2, Trial 3, Trials 1–5 Total, List B; p s < .007), with no significant cohort differences found on the delayed-recall trials. As expected, education level, age group, and ethnicity were significant predictors of CVLT performance ( p s < .01). Importantly, however, there were no interactions between cohort year of norms collection and education level, age group, or ethnicity on performance. Conclusions: The clinical implications of the present findings for using word list learning and memory tests like the CVLT, and the potential role of socioenvironmental factors on the observed negative Flynn effect on the attention/working memory and learning trials, are discussed.